Calculated data from sensor Q3 at Maisbich for month 2004-03 - W.M.J.(Wim) Luxemburg; Cees-Anton van den Dool (4TU.Centre for Research Data, 2009)
Height notch above sensor 0.0015m
Parent item:
Maisbich (Luxemburg), calculated data from discharge meter Q3, 2003-12 to 2006-10
Measuring instrument:
Maisbich basin: V-notch discharge meter Q3 (Qdown)
Type: Pressure Sensor Keller DCX-4.0, SN 1467
This instrument is based on differential pressure measurement of two
absolute sensors. The sensors measure pressure and temperature.
Height of V-notch above sensor: -0.0015m.

Datasets with correction contain the corrected discharge observed at the Vnotch.
The discharge is calculated as Q=Cd*h^2.5
After correcting the logger measurements with hand measured depths we interpolated the difference (dH)
Then we determined the factor Cd with discharge measurements which we also interpolated
The timing of hand measurements can be corrected to better represent the logged values

The last corrections (variable "clean_corr") were made for blocking of the V-notch weir as folows:
z1 represents the last good discharge value after which sedimentation slowly starts blocking the weir
z2 represents the moment when the blocking is max
z3 represents the moment just before cleaning of the weir
z4 represents the moment after cleaning of the weir
The max difference in discharge is Q(z3)-Q(z4)
Contributor: Durr, E.H.(Eugene)
Keywords: Physical Geography and Environmental Geoscience; Collection: Darelux - River Environment Luxemburg; Time: 2004-03